Corrigendum to “Surviving the Tide: Assessing Guiana dolphin persistence amidst growing threats in a protected estuary in South-eastern Brazil” [J. Nature Conserv. 82 (2024) 126713] (Journal for Nature Conservation (2024) 82, (S1617138124001626), (10.1016/j.jnc.2024.126713)) - de Almeida, Inaê Guion; Percequillo, Alexandre Reis; Rollo, Mario Manoel [UNESP] (Elsevier, 2024)
The authors regret that the affiliation for Mario Manoel Rollo Jr. was not fully included. The correct affiliations are updated as above. The authors would like to apologise for any inconvenience caused.